The Cognitive, Behavioral, and Emotional Aspects of Eating Habits and Association With Impulsivity, Chronotype, Anxiety, and Depression: A Cross-Sectional Study - Aoun, Carla; Nassar, Lynn; Soumi, Stéphanie; El Osta, Nada; Papazian, Tatiana; Rabbaa Khabbaz, Lydia (Frontiers in Behavioral Neuroscience, 2019)
Background and objectives: Understanding behavioral issues associated with eating would provide important insight into obesity development and possibly procure ways to prevent its occurrence or to treat it. This study's objectives were to examine links between cognitive, behavioral, and emotional aspects of eating habits and chronotype, impulsivity, anxiety, and depression among university students. Subjects and methods: The following questionnaires were used: TFEQ-R 18, UPPS-short, HADS, and MEQ. All participants gave their informed written consent prior to enrolment. Results: Among females, increased BMI was associated to uncontrolled eating and emotional eating, while in males, BMI was associated to emotional eating only. In males, no associations of BMI with impulsivity were found while in females they were present. Chronotype scores were positively correlated to cognitive restraint and negatively to uncontrolled eating among males. No associations were found for females. CR was lower among females with higher depression scores, while higher anxiety scores were associated to UE among males. Conclusions: This was a cross-sectional study of three cognitive and emotional domains related to eating habits among university students (young adults). Results showed significant correlations between BMI, TFEQ-R18 scores, impulsivity and anxiety or depression. Future studies should replicate findings in samples of individuals with different aspects of eating disorders such as binge eating disorder, food addiction or bulimia nervosa.